2005
DOI: 10.1186/1743-422x-2-60
|View full text |Cite
|
Sign up to set email alerts
|

HBx M130K and V131I (T-A) mutations in HBV genotype F during a follow-up study in chronic carriers

Abstract: T-A mutations were found in HBV genotype F in chronic carriers but not in patients who recovered from acute infection. These mutations could be developing early during infection although the possibility of infection with the mutant virus could not be excluded. More studies are necessary to establish if the T-A mutation can be used as a prognostic marker for severity of liver disease in patients infected with HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 35 publications
2
1
0
1
Order By: Relevance
“…We identified high frequency of K130M mutation and A1762T/G1764A double-mutation in 47 para-tumor and central-tumor samples, similar to previous reports [20,32,33]. But no statistically significant differences in these mutation sites were observed between central- and para-tumor tissues, although there were differences in entropy between both sequence datasets.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We identified high frequency of K130M mutation and A1762T/G1764A double-mutation in 47 para-tumor and central-tumor samples, similar to previous reports [20,32,33]. But no statistically significant differences in these mutation sites were observed between central- and para-tumor tissues, although there were differences in entropy between both sequence datasets.…”
Section: Resultssupporting
confidence: 89%
“…This study detected a high frequency of K130M mutation and A1762T/G1764A double-mutation (approximately 2/3), consistent with previous reports [20,32,33]. But by using conventional data analysis method, no difference in the calculated amino acid frequency or selection between central- and para-tumor isolates was found, which is also consistent with previous study [53].…”
Section: Discussionsupporting
confidence: 92%
“…HBx with mutations in amino acids 130 and 131 have been frequently reported and may be associated with the severity of chronic hepatitis; these mutations have also been detected in HCC (Yotsuyanagi et al, 2002;Iavarone et al, 2003;Leon et al, 2005), and a recent study of serum samples indicated that these mutations arise before the development of HCC (Kuang et al, 2004). However, the functional consequences of these mutated HBx proteins are still unclear.…”
Section: Hbv-related Hcc D Kremsdorf Et Almentioning
confidence: 99%
“…Penentuan asam amino dengan metode deduksi secara manual dibandingkan dengan urutan parsial asam amino RT DNA polimerase dan protein S HbsAg. Genotipe isolat ditentukan dengan membandingkan hasil sekuensing dengan urutan nukleotida homolog yang didapat dari data GenBank, menggunakan program BLAST (Leon et al, 2005).…”
Section: Analisis Hasil Sekuensingunclassified